Association of additives in supplemented grazing cattle during the finishing phase at the rainy season - Dallantonia, Erick Escobar [UNESP]; Silva, Lorrayny Galoro da [UNESP]; Granja-Salcedo, Yury Tatiana; Messana, Juliana Duarte [UNESP]; Brito, Liziane de Figueiredo [UNESP]; Lima, Ana Rebeca Castro [UNESP]; Vito, Elias San; Castagnino, Pablo de Souza [UNESP]; Sobrinho, Americo Garcia da Silva [UNESP]; Reis, Ricardo Andrade [UNESP]; Berchielli, Telma Teresinha [UNESP] (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2023)
The objectives were to evaluate the effects of monensin and virginiamycin, alone or combined, on supplemented Nellore cattle grazing tropical grass during the rainy season. Two experiments were conducted simultaneously to evaluate intake, digestibility, CH4 emissions, blood parameters, performance, and carcass characteristics (Exp. 1), and ruminal fermentation and relative abundance of ruminal microorganisms (Exp. 2). Animals (n = 92 Exp. 1 and n = 12 Exp. 2) were distributed in a completely randomized design and allocated in twelve paddocks composed of Urochloa brizantha (A. Rich.) Stapf. cv. Xaraes. A protein-energetic supplementation of 3 g/kg of BW per day was provided to all animals. Supplements were: without additives (WA), monensin alone at 80 mg/kg of product (MN), virginiamycin alone at 150 mg/kg of product (VM), and monensin (80 mg/kg of product) combined with virginiamycin (150 mg/kg of product; MNVM). Treatments did not affect intakes of total dry matter (DM), supplement DM, and nutrients. However, the intakes of forage DM and crude protein decreased in cattle fed MNVM compared with animals fed WA, MN, and VM. Total volatile fatty acids increased in animals fed VM. Ruminal NH3-N decreased, and pH increased in animals fed MN, VM, and MNVM. Relative abundance of total F. succinogenes and S. ruminantium decreased and R. flavefaciens increased in animals fed MN and VM at d 118. Treatments had no effect on enteric CH4 emissions. The average daily gain (ADG) and total gain were greater in cattle fed MNVM than in cattle fed MN. Combination of monensin and virginiamycin altered the rumen microbial populations but did not decrease enteric CH4 emissions. However, it decreased forage dry matter intake without altering the ADG and total weight gain, leading to an increase in feed efficiency. Results from this study indicate an advantage in including feed additives combined in the diet of supplemented Nellore cattle grazing tropical grass during the rainy season.
Keywords: meat quality; methane; monensin; pasture; performance; virginiamycin